1997
DOI: 10.1021/ci960049h
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Connectivity Index:  A Novel Highly Discriminating Topological Descriptor for Structure−Property and Structure−Activity Studies

Abstract: A novel, distance-cum-adjacency topological descriptor, termed as eccentric connectiVity index, has been conceptualized, and its discriminating power has been investigated with regard to physical/biological properties of molecules. Correlation coefficients ranging from 95% to 99% were obtained using eccentric connectivity index in various datasets with regard to physical properties of diverse nature. These correlations were far superior to those correspondingly derived from the Wiener index. For structure-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
180
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(180 citation statements)
references
References 20 publications
(30 reference statements)
0
180
0
Order By: Relevance
“…In this work, the quantity, W e , eventually named the Wiener index or Wiener number, was introduced for the first time, and he showed that there are excellent correlations between W e and a variety of physico-chemical properties of organic compounds. Another distance-based topological index of the graph G is the eccentric-connectivity index, ξ(G), which is defined as [5] …”
Section: Definitions and Notationsmentioning
confidence: 99%
“…In this work, the quantity, W e , eventually named the Wiener index or Wiener number, was introduced for the first time, and he showed that there are excellent correlations between W e and a variety of physico-chemical properties of organic compounds. Another distance-based topological index of the graph G is the eccentric-connectivity index, ξ(G), which is defined as [5] …”
Section: Definitions and Notationsmentioning
confidence: 99%
“…Several such indices (see, for example, [5,8] ) have been introduced and investigated subsequently. The eccentric connectivity index is a parameter recently introduced [10] and subsequently studied (see for example [2,6,7,11,13]) with regard to physical / biological properties of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…We now recall needed notions, such as regular dendrimer, eccentric connectivity index [10], eccentric connectivity polynomial [14] and others. For unexplained notions and notations, we refer to [3].…”
Section: Introductionmentioning
confidence: 99%
“…Karelson et al and Katrizky et al reviewed the earlier physicochemical, topological, geometrical and constitutional descriptors in QSPR studies, including the methods for boiling-point estimations of diverse organic compounds [18]. Sharma et al [19] and Kier et al [20] used topological and electrotopological descriptors for predicting normal boiling points of 34 and 21 amines by MLR method, respectively. Compared with the previous work, the data set used in our investigation is more diverse and the developed model is more general, stable and practicable.…”
Section: Introductionmentioning
confidence: 99%